La inclusión educativa: una aproximación a las prácticas en España y Portugal (Revista Lusófona de Educação, 2026)
Educational Inclusion: An Approach to Practices in Spain and PortugalAbstract: Spain and Portugal committed to achieving educational inclusion, but educational practice still present significant challenges in its implementation. Despite legislative advances, inclusion remains limited, making it difficult to meet international commitments. This research is aimed to analyse the impact of two perspectives on educational inclusion: the psychological one, which focuses on the subjects and their learning, and the pedagogical one, focused on the didactic and organizational proposal. A qualitative methodology was used, specifically documentary research and interview. The results show that Portugal has more advanced legislation than Spain but educational practices in both countries are homogeneous and segregating. Students are separated into special education classrooms or support centres; in other cases, they receive specific attention inside or outside the classroom. In conclusion, although legislation recognizes the autonomy of educational centres and promotes flexibility, the success of inclusion depends largely on teachers. Those must have the ability and compromise with diversity, as observed in the inclusive practices of the Modern School Movement.Keywords: Educational legislation; Educational support; Inclusion; Segregation.